A critical refection on the enablers of transformative health promotion action. (30th September 2020) - Barry, M
Abstract: The goal of ensuring that all human beings can have healthy lives and can maximise their health potential calls for concerted action on health promotion as an integral component of modern health systems and public policy. In addressing current health and global challenges, there is an urgent need to move beyond the rhetoric of health promotion towards concrete action and strengthening the capacity of countries to implement health promotion at a political, policy and service delivery level. This presentation reviews progress to date and critically considers the enabling mechanisms and system requirements for transformative health promotion actions that can improve the capacity of health and social systems to improve population health and wellbeing, reduce health inequities, and realise the ambitions of the SDGs and the right to health for all. Drawing on a recent report prepared for the European Commission, this presentation discusses what actions are needed to strengthen health promoting policies, research and practices that support a whole-of-government and whole-of-society approach. This presentation makes the case for investing in transformative actions for improved health and wellbeing. Health promotion needs to be placed at the centre of the health policy and sustainable development agenda in order to enhance the resilience of health systems, improve health equity, and make health promotion practices and actions integral to the global health and wellbeing agenda.